Serum copper and zinc levels at diagnosis and hepatocellular carcinoma survival in the Guangdong Liver Cancer Cohort - Fang, Ai‐Ping; Chen, Pei‐Yan; Wang, Xiao‐Yan; Liu, Zhao‐Yan; Zhang, Dao‐Ming; Luo, Yun; Liao, Gong‐Cheng; Long, Jing‐An; Zhong, Rong‐Huan; Zhou, Zhong‐Guo; Xu, Yan‐Jun; Xu, Xiao‐Jun; et al. (International journal of cancer, 2019)
Copper and zinc are essential micronutrients, whose imbalance may be involved in the development and progression of cancer. However, the role of copper and/or zinc imbalance in the prognosis of hepatocellular carcinoma (HCC) is currently unclear. Our objective was to investigate the association between serum levels of copper, zinc and their ratio (copper/zinc) at diagnosis with HCC survival. We included 989 patients with incident HCC in this prospective cohort study, who were enrolled in the Guangdong Liver Cancer Cohort (GLCC) study within 30 days of diagnosis between September 2013 and February 2017. Serum copper and zinc were measured using inductively coupled plasma mass spectrometry. Primary outcomes were liver cancer‐specific survival (LCSS) and overall survival (OS). Cox proportional hazards models were used to calculate the multivariable hazard ratios (HRs) and 95% confidence interval (CI). Higher serum copper levels were strongly associated with worse LCSS (Q4 vs. Q1: HR = 1.87, 95% CI: 1.22–2.86; p < 0.01 for trend) and OS (Q4 vs. Q1: HR = 2.06, 95% CI: 1.36–3.11; p < 0.01 for trend). The calculated copper/zinc ratio was positively associated with LCSS (Q4 vs. Q1: HR = 1.31, 95% CI: 0.89–1.92; P = 0.04 for trend) and OS (Q4 vs. Q1: HR = 1.43, 95% CI: 0.99–2.08; P = 0.01 for trend). No overall associations were observed between serum zinc levels and LCSS or OS in the entire cohort. The results suggest that higher serum copper and copper in relation to zinc levels (i.e., higher copper/zinc ratio) may be associated with worse HCC survival, but serum zinc levels may be not associated with HCC survival. What's new? Copper and zinc are essential micronutrients whose imbalance may be involved in development and progression of cancer. Currently, the role of copper and/or zinc imbalance in the prognosis of hepatocellular carcinoma (HCC) however remains unclear. The authors examine for the first time whether serum levels of copper, zinc, and their ratios are associated with survival in a large prospective cohort of newly diagnosed patients. The findings suggest that higher copper levels and copper/zinc ratios are associated with worse survival, but serum zinc levels are not associated with HCC survival. The results may have important implications for the prognosis of HCC.